Some fixed point results in rectangular metric spaces - Sarita Devi; Pankaj (Annals of Mathematics and Physics - Peertechz Publications, 2023)
After motivation from Geraghty-type contractions and of Farhan, et al. we define α-admissible mappings and demonstrate the fixed point theorems for the above-mentioned contractions in rectangular metric space in this study. In the end, we discuss some consequences of our results as corollaries.  2010 MSC: 47H10, 54H25.